Macroeconomics and Monetary Economics - 2: Array - Collective Authors, (Acta Universitatis Danubius. Œconomica, 2021)
The previous article analized the phenomenon of work for developing countries and regions of the World for each of the developing countries or regions of the World. A number of indicators are analyzed, such as: Labor force, Labor force with advanced education, Employment in agriculture, industry and services and also the phenomenon of unemployment.